2006
DOI: 10.1007/s10725-006-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Stable Agrobacterium-mediated transformation of embryogenic tissues from Pinus pinaster Portuguese genotypes

Abstract: Protocols for genetic transformation of maritime pine (Pinus pinaster Sol. ex Aiton) embryogenic tissues were developed using the Agrobacterium C58pMP90/pPCV6NFGUS. This is the first report of Agrobacterium-mediated T-DNA integration in P. pinaster confirmed by Southern blot analysis. The omission of casein hydrolysate from culture medium during cocultivation and subsequent subculture was crucial to control Agrobacterium growth. Two different transformation protocols were compared: (1) bacterial drops were spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…They reported functional GUS gene expression in transgenic pears even after cryopreserved for 1 year. Similar types of observations were reported by Tereso et al (2006). They also reported that transgenic maritime pine (Pinus pinaster Sol.…”
Section: Introductionsupporting
confidence: 85%
“…They reported functional GUS gene expression in transgenic pears even after cryopreserved for 1 year. Similar types of observations were reported by Tereso et al (2006). They also reported that transgenic maritime pine (Pinus pinaster Sol.…”
Section: Introductionsupporting
confidence: 85%
“…Somatic embryo maturation was performed as described by Tereso et al (2006), except that plant growth regulatorfree DCR medium supplemented with 3% of sucrose and 1% activated charcoal, was used for resuspension of embryogenic tissues. Embryogenic suspensions were then spread over filter papers and placed on maturation medium.…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…Conversion of somatic embryos to plants growing in the greenhouse (emblings) was obtained following the protocol described by Tereso et al (2006). Emblings with a welldeveloped epicotyle were transferred to a mixture of peat:perlite:pine tree bark (1:1:1) and acclimatized in a growth chamber over a 10-day period (Miguel et al 2004).…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…The whole process from ET to transgenic plantlet(s) takes significantly less time than organogenesis from other explants. In addition, transformed ETs can be easily cryopreserved without compromising re-growth and transgene expression (Tereso et al, 2006). This is an important advantage because some P. abies ET cultures progressively lose their maturation potency already after 6 months (Högberg et al, 1998).…”
Section: Resultsmentioning
confidence: 99%